Exploring Students’ Self-Regulated Learning Strategy in Online Learning - Arrafii, Mohammad Arsyad (Sumber Belajar Sejahtera, 2025)
One of the impacts of the COVID-19 pandemic on higher education is the acceleration of online learning. Consequently, there has been a drastic change in the interaction patterns between students, instructors, and learning resources. Students must be more independent and creative in seeking, processing, utilizing various learning resources, and addressing learning challenges. In such situations, self-regulated learning (SRL) skills are crucial. However, SRL strategies in the context of online learning in Indonesia still need a comprehensive exploration. This study aims to explore students’ SRL strategies and its components among Indonesian students in online learning context, employing the Online Self-regulated Learning Questionnaire (OSLQ) (Barnard et al., 2009). The questionnaire was translated into Indonesian and piloted on a limited scale before being distributed to the main respondents of 236 students from various universities on Lombok Island. Descriptive statistics and Exploratory Factor Analysis (EFA) were used to address the research questions. Statistical analysis shows that students employ a variety of SRL strategies, but only ‘environment structuring’, which involves efforts to condition time and place for a comfortable and conducive online learning environment, was used most frequently. Additionally, EFA revealed five components of SRL strategies, with only one component being dominant. The implications for practice, particularly in the context of ongoing and post-pandemic education scenarios, are discussed, emphasizing the need for adaptive, technologically supported learning strategies that accommodate the dynamic nature of online education